Combining dispositions and evaluations of vocation and job to account for counterproductive work behavior in adolescent job apprentices - Marcus, Bernd [Verfasser]; Wagner, Uwe [Verfasser] (My University, 2007)
The present paper "investigated the joint impact of selected antecedents of counterproductive work behavior (CWB). A sample of 272 German apprentices (age range 15-23 years) reported on their CWB and completed measures of situational evaluations (vocational preference, level and constructiveness of job satisfaction) believed to trigger CWB and of dispositional motivators (measured by integrity test subscales) and controls (self-control and another subset of integrity scales) of CWB. All predictors investigated showed the expected bivariate relationships with CWB. Multivariate analyses revealed that the triggering effect of an unfavorable vocational choice on CWB was fully mediated by job satisfaction. When predictors were aggregated, a composite of dispositional control variables had the largest effect on CWB and moderated the effects of motivational dispositions and situational evaluations." (PSYNDEX)
Keywords: P 2.3 Auszubildende; G 1.3.2 Bildungsverhalten und -verläufe; Auszubildender; Ausbildungszufriedenheit; Ausbildungsmotivation; Arbeitsverhalten; Einflussfaktor; Berufswahl; Multivariate Analyse